Impact of a multivariate serum-based proteomic test on physician treatment recommendations for advanced non-small-cell lung cancer. (3rd June 2017) - Akerley, Wallace L.; Arnaud, Alix M.; Reddy, Bibas; Page, Ray D.
Abstract: Objective: The VeriStrat 1 (VS) test is intended to help guide treatment decisions for patients with advanced non-small-cell lung cancer (NSCLC) without an EGFR-sensitizing mutation, classifying patients into two categories. Patients classified as VSGood have a favorable prognosis and significant clinical response to EGFR tyrosine kinase inhibitors (TKIs). Patients classified as VSPoor have a less favorable prognosis and exhibit no significant response to EGFR -TKIs. The objective of this paper is to assess the real-world impact of VS test results on physicians' treatment recommendations including referrals for best supportive care (BSC). Methods: Between 1 January 2012 and 1 November 2016, physician respondents were asked to complete standardized questionnaires before and after receiving VS results in patients meeting criteria for the intended use of the VS test. This study evaluated three endpoints: whether physicians followed VS test results in making treatment recommendations, the extent to which tests results changed these treatment recommendations, and the patterns of care subsequent to VS testing. Results: Of the tests ordered by 989 physicians, 2494 VS tests had completed treatment recommendation questionnaires both prior to and after testing. Prior to VS testing, physicians were considering treatment with EGFR -TKIs for 2250 patients (90%). The VS test classified 1950 patients as VSGood and 544 patients as VSPoor. For patients classified as VSPoor, physicians recommended BSC for 25% of patients and standard systemic treatments such as chemotherapies for 65% of patients. Consistent with previous publications, physicians recommended EGFR -TKI therapy for only 10% of VSPoor patients but for 89% of VSGood patients. Overall, physician's treatment recommendations were consistent with test results in 98% of cases. Availability of test results decreased ineffective treatment recommendations by 89% for VSPoor patients. Conclusions: Among physicians ordering VS, the test significantly influenced treatment recommendations for patients with NSCLC, reducing ineffective and expensive treatment at the end of life.